The Accuracy and Perception of Test-Based Management of Malaria at Private Licensed Chemical Shops in the Middle Belt of Ghana - Kwarteng, Anthony (Am J Trop Med Hyg, 2019)
The sale of artemisinin-based combination therapy (ACT) by private licensed chemical shops (LCS) without testing is contrary to current policy recommendations. This study assessed the accuracy and perception of test-based management of malaria using malaria rapid diagnostic test (mRDT) kits at private LCS in two predominantly rural areas in the middle part of Ghana. Clients presenting at LCS with fever or other signs and symptoms suspected to be malaria in the absence of signs of severe malaria were tested with mRDT by trained attendants and treated based on the national malaria treatment guidelines. Using structured questionnaires, exit interviews were conducted within 48 hours and a follow-up interview on day 7 (±3 days). Focus group discussions and in-depth interviews were also conducted to assess stakeholders’ perception on the use of mRDT at LCS. About 79.0% (N = 1,797) of clients reported with a fever. Sixty-six percent (947/1,426) of febrile clients had a positive mRDT result. Eighty-six percent (815/947) of clients with uncomplicated malaria were treated with the recommended ACT. About 97.8% (790/808) of clients with uncomplicated malaria treated with ACT were reported to be well by day 7. However, referral for those with negative mRDT results was very low (4.1%, 27/662). A high proportion of clients with a positive mRDT result received the recommended malaria treatment. Test-based management of malaria by LCS attendants was found to be feasible and acceptable by the community members and other stakeholders. Successful implementation will however require effective referral, supervision and quality control systems.